2019
DOI: 10.1002/ece3.5322
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantages and benefits of evolved unicellularity versus multicellularity in budding yeast

Abstract: Multicellular organisms appeared on Earth through several independent major evolutionary transitions. Are such transitions reversible? Addressing this fundamental question entails understanding the benefits and costs of multicellularity versus unicellularity. For example, some wild yeast strains form multicellular clumps, which might be beneficial in stressful conditions, but this has been untested. Here, we show that unicellular yeast evolve from clump‐forming ancestors by propagating samples from suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 46 publications
(91 reference statements)
1
42
0
Order By: Relevance
“…Previous studies have reported that wild type yeast cluster strains were resistant to free/thaw treatment (Kuzdzal-Fick et al, 2019) and the stress resistance was measured using a cell counter. In contrast, in the present study, we used spot assay to investigate the sensitivity of yeast cluster phenotype to cold (20°C) and heat stress (37°C).…”
Section: Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that wild type yeast cluster strains were resistant to free/thaw treatment (Kuzdzal-Fick et al, 2019) and the stress resistance was measured using a cell counter. In contrast, in the present study, we used spot assay to investigate the sensitivity of yeast cluster phenotype to cold (20°C) and heat stress (37°C).…”
Section: Heat Stressmentioning
confidence: 99%
“…Several past studies have examined the evolution of multicellular snowflake clusters from unicellular yeast S. cerevisiae (Ratcliff et al, 2012, Ratcliff et al, 2013, Koschwanez et al, 2011a, Rebolleda-Gomez et al, 2012, Driscoll & Travisano, 2017, Jacobeen et al, 2018, Rebolleda-Gomez & Travisano, 2018, Kuzdzal-Fick et al, 2019, Herron et al, 2019. The studies have demonstrated that, under selection, the transition from unicellular to multicellularity is relatively quick (of the order of a few dozen generations).…”
Section: Introductionmentioning
confidence: 99%
“…Cells may also aggregate by surface attachment and by active movement toward groups. Many possible costs and benefits of cellular aggregation occur [18][19][20][21][22] . However, heat in microbial aggregates has not been widely discussed.…”
Section: Individual and Group Traitsmentioning
confidence: 99%
“…Cells may also aggregate by surface attachment and by active movement toward groups. Many possible costs and benefits of cellular aggregation occur [19][20][21][22][23] . However, heat in microbial aggregates has not been widely discussed.…”
Section: Individual and Group Traitsmentioning
confidence: 99%